Women’s Representation in Peace Processes: A Discursive Analysis of the UNSCR 1325 - Mboumien, Sally Maforchi; Fomukong, Seino Evangeline Agwa; Tafopi, Djimeli Alexandre (Advances in Social Sciences Research Journal, 2023)
This paper aims to address the critical issue of the representation of women in peace processes, particularly in conflict-affected areas of Cameroon, from the perspective of language use and the translation of the provisions of the Women, Peace, and Security (WPS) agenda in daily actions. The study employs a discursive analysis of the WPS agenda, guided by the Discourse Historical Approach by Wodak and Reseigl and Feminist Critical Discourse Analysis. Data was a document review of the UNSCR1325 of October 2000. The investigation revealed that language use in the policy document shapes the representation of women of peace processes. The finding of the study contributes to the understanding of the representation of women in peace processes and reveals that language use in texts and talks around women, peace, and security policy practice is contributing to the low representation of women in peace processes. The study highlights the importance of identifying discourses in texts and provides a framework for future studies to examine language use in different contexts and expand the discourse analysis techniques employed.